Mediatization of Islam in Kashmir: A Critical Content Analysis of Contemporary Islamic Socio-Religious Magazines - Dr John Koyye Babu; Muntaha Mehraj Hafiz (Medya ve Din Araştırmaları Dergisi)
This paper provides an in-depth analysis of select magazines published by Islamic socio-religious organizations in Kashmir, India. It explores various aspects of these publications, including thematic prevalence, framing techniques, symbolic representation, tone, and the portrayal of religion and faith. Using both qualitative and quantitative approaches, along with content analysis, this study applies Ninian Smart's Seven Dimensions of Religion as its primary theoretical and methodological framework. Key findings highlight recurring themes of ethics, social justice, and community solidarity, alongside the use of persuasive language and rhetorical techniques such as repetition, symbolism, and imagery. The magazines portray religion as a source of guidance and compassion, with ethical and social themes (64.5%) prominently featuring topics like proper conduct, human rights, women's rights, Islamic law, social issues, and community relations. Overall, the positive tone of the publications underscores the role of Islamic magazines in fostering community cohesion and influencing public discourse within Kashmir. This study is of notable relevance for religious practitioners and offers valuable insights for government agencies aiming to engage with Islamic organizations in the region, promoting collaborative approaches to address community needs and inform policy development.